Kajian Agronomis dan Kualitas Tepung Berbahan Ubi Kayu Lokal - Lucky Hartanti; Anang Syamsunihar; Ketut Anom Wijaya (Pro Food, 2017)
Cassava flour has a good potential to substitute wheat flour for various food products and have a good opportunity to developed. The farmers prefer to cultivate local types of cassava compared to superior varieties national. Fresh cassavas contain cyanide acid (HCN), which is harmful to health. Knowledge and skills in processing of cassava is needed to produce fresh cassava become safety product. The aimed of this research was to conducted to: 1) Examine the agronomic potential of local cassava as raw material for cassava flour industry , 2) Study quality cassava flour produced from three different types of local cassava. Cassava used in this study was a local type i.e.: “ketan”, “Pb”, “Sambung”. The method of processing cassava flour was dried cassava method “gaplek”, wet method “tapioka fermentation method “mocaf”. In general all types of local cassava had a good agronomic potential and safe to be processed into cassava flour. Mocaf from “Pb” type gave the best result. The best tapioca was produced from “ketan” type of cassava. Key Words: Cassava Flour, HCN, Local Types of Cassava ABSTRAK Tepung ubi kayu mampu menggantikan tepung terigu untuk berbagai produk pangan dan berpeluang bagus untuk dikembangkan. Petani lebih suka membudidayakan ubi kayu jenis lokal dibandingkan dengan varietas unggul nasional. Ubi kayu segar mengandung HCN yang berbahaya bagi kesehatan. Diperlukan teknik yang baik untuk mengolah ubi kayu menjadi produk yang aman dikonsumsi oleh masyarakat. Tujuan penelitian ini adalah: 1) Mengkaji potensi agronomis ubi kayu jenis lokal sebagai bahan baku industri tepung ubi kayu.2) Mengkaji kualitas tepung ubi kayu yang dihasilkandari tiga jenis ubi kayu lokal yang berbeda Ubi kayu yang dipakai dalam penelitian adalah ubi kayu lokal jenis ketan, Pb dan ubi sambung. Metode pengolahan tepung ubi kayu yang dilakukan adalah metode kering gaplek, metode basah tapioca dan metode fermentasi mocaf. Secara umum semua ubi kayu jenis lokal berpotensi agronomis dan aman untuk diolah menjadi tepung ubi kayu. Mocaf dari ubi jenis Pb memberikan hasil terbaik. Tapioka terbaik dihasilkan dari ubi kayu jenis ketan. Kata Kunci :HCN, Tepung ubi kayu, Ubi kayu lokal